Cost of stroke in France. Issue 7 (8th April 2013) - Chevreul, K.; Durand‐Zaleski, I.; Gouépo, A.; Fery‐Lemonnier, E.; Hommel, M.; Woimant, F.
<x xml:space="preserve">Abstract</x> Background and purpose A cost of illness study was undertaken on behalf of the French Ministry of Health to estimate the annual cost of stroke in France with the goal of better understanding the current economic burden so that improved strategies for care may be developed. Methods Using primary data from exhaustive national databases and both top‐down and bottom‐up approaches, the stroke‐related costs for healthcare, nursing care and lost productivity were estimated. Results The total healthcare cost of stroke patients in France in 2007 was €5.3 billion, 92% of which was borne by statutory health insurance. The average cost of incident cases was €16 686 per patient in the first year, while the annual cost of prevalent cases was a little less than half that amount (€8099). Nursing care costs were estimated at €2.4 billion. Lost productivity reached €255.9 million and that income loss for stroke patients was partially compensated by €63.3 million in social benefit payments. Conclusions With healthcare costs representing 3% of total health expenditure in France, stroke constitutes an ongoing burden for the health system and overall economy. Nursing care added nearly half again the amount spent on healthcare, while productivity losses were more limited because nearly 80% of acute incident strokes were in patients over age 65. The high cost of illness underscores the need for improved prevention and interventions to limit the disabling effects of stroke.